A Comparative Atlas-Based Recognition of Mild Cognitive Impairment With Voxel-Based Morphometry - Long, Zhuqing; Huang, Jinchang; Li, Bo; Li, Zuojia; Li, Zihao; Chen, Hongwen; Jing, Bin (Frontiers in Neuroscience, 2018)
An accurate and reliable brain partition atlas is vital to quantitatively investigate the structural and functional abnormalities in mild cognitive impairment (MCI), generally considered to be a prodromal phase of Alzheimer’s disease (AD). In this paper, we proposed an automated structural classification method to identify MCI from healthy controls (HC), and investigated whether the classification performance was dependent on the brain parcellation schemes, including Automated Anatomical Labeling (AAL-90) atlas, Brainnetome (BN-246) atlas and AAL-1024 atlas. In detail, structural magnetic resonance imaging (sMRI) data of 69 MCI patients and 63 HC matched well on gender, age and education level were collected and analyzed with voxel-based morphometry (VBM) method firstly, then the volume features of every region of interest (ROI) belonging to the above-mentioned three atlases were calculated and compared between MCI and HC groups respectively. At last, the abnormal volume features were selected as the classification features for a proposed support vector machine based identification method. After the leave-one-out cross-validation to estimate the classification performance, our results reported accuracies of 83%, 92% and 89% with AAL-90, BN-246 and AAL-1024 atlas respectively, suggesting that future studies should pay more attention to the selection of brain partition schemes in the atlas-based studies. Furthermore, the consistent atrophic brain regions among three atlases were predominately located at bilateral hippocampus, bilateral parahippocampal, bilateral amygdala, bilateral cingulate gyrus, left angular gyrus, right superior frontal gyrus, right middle frontal gyrus, left inferior frontal gyrus and left precentral gyrus.